ICF-CY based assessment tool for children with autism. (April 2013) - Gan, Shu-Mei; Tung, Li-Chen; Yeh, Chun-Yu; Wang, Chun-Hou
<x xml:space="preserve">Abstract</x> Purpose: The objectives of this study was to develop an International Classification of Functioning, Disability and Health-Children and Youth (ICF-CY) based questionnaire for children with autism, investigate the inter-rater reliability of the questionnaire and assess functional performance in children with autism. Method: The ICF-CY based questionnaire for children with autism comprised 118 items was designed with reference the ICF-CY structure. The study protocol was divided into two parts. In the first part, the inter-rater reliability of the questionnaire was investigated using information from 26 children (aged 3–6 years) with autism and using the intra-class correlation coefficients to estimate reliability. The second part of the study aimed to assess functional performance of another independent sample (136 children, aged 3–6 years) utilizing the questionnaire. Mean scores were compared by nonparametric statistic. Results: The inter-rater reliability for each domains of the questionnaire was found to be moderate to high (intra-class correlation coefficients ranged from 0.72 to 0.97). Children with autism had major problems in voice and speech functions. They had high dependency when executing individual activities of learning and applied knowledge. They also required maximal assistance while engaging in social activities related to conversation and major life categories. Conclusions: This preliminary study shows that ICF-CY based questionnaire has good reliability and can reflect the functional profile of preschool children with autism. However, further study is needed to confirm other psychometric characteristics.